The Relative Contribution Of Academic Subjective Well-Being In Predicting Citizenship Values Among King Khalid University Students - Ibrahim, Asem M.; Teleb, Ahmad A.; Abdelmagid, Ahmad S.; Soliman, Amro M. (Migration Letters, 2024)
The research aimed to discern the correlation between academic subjective well-being (ASW) and citizenship values (CV), and to ascertain the extent of relative contribution of ASW to predicting CV ​​among King Khalid University (KKU) students. To achieve the research objectives, the descriptive method was used, both correlational and comparative. The researchers developed scales for ASW and CV, administered to a sample of 134 students (67 males and 67 females) with ages ranging from 18 to 45 years, representing various programs at KKU. Pearson’s correlation coefficient, simple regression analysis (using the Enter method), and multiple regression analysis (using the Stepwise method) were employed for data analysis. The research findings highlighted a positive and statistically significant correlation between ASW and CV. Furthermore, the study demonstrated that ASW, with its four dimensions, plays a predictive role in determining CV within the research sample.